El concepto de lebenswelt : Seminario Permanente de Fenomenología - López Sáenz, Mari Carmen; Uscatescu Barrón, Jorge; Sánchez Benítez, Sergio; Díaz Álvarez, Jesús Miguel; Hermida Lazcano, Pablo (Investigaciones Fenomenológicas, 1995)
-